P372 Effectiveness and safety of immunosuppressants for pouch disorders: results from the RESERVO Study of GETECCU. (27th May 2021) - Mesonero Gismero, F; Zabana, Y; Fernández-Clotet, A; Leo, E; Caballol, B; Núñez, A; García, M J; Bertoletti, F; Mínguez, A; Suris, G; Casis, B; Ferreiro-Iglesias, R; et al.
Abstract: Background: Pouchitis and other inflammatory disorders of the pouch (IDP), such as Crohn′s-like disease of the pouch (CDP), are frequent in patients operated for a previous diagnosis of ulcerative colitis. Many different therapies have been used, but the effectiveness of immunosupresants (IMM) has been poorly explored in this setting. Our aim was to evaluate the use, efficacy and safety of IMM in patients with pouchitis or another IDP. Methods: Retrospective and multicentric study of a Spanish cohort of pouch-carrying patients with previous diagnosis of ulcerative colitis, and subsequent diagnosis of IDP, following ECCO diagnostic criteria. Patients who used IMM to treat these conditions were selected. Clinical effectiveness was evaluated at long-term. We defined clinical remission as returning to the previous stool frequency, no pain or defecatory urgency, clinical response as the improvement in these parameters without the achievement of remission, and non-response as no improvement or worsening symptoms. Endoscopic response was evaluated when possible using modified pouchitis disease activity index (PDAI) endoscopic subscore. Adverse events were collected. We used descriptive statistics. Results: In the overall cohort of 338 patients with IDP, 93 (27%) were treated with IMM. Of those, 57% males, median age 40 (20-71) ys, and 72% non-smokers. Colectomy was performed at a median age of 31 (18-63) ys and IPD was diagnosed 25 (1-235) months after ileostomy closure. IMM used were thiopurines (n=86), methotrexate (n=4), cyclosporine (n=2) and tacrolimus (n=1). IMM were used as monotherapy in 66 (71%) cases and were indicated as treatment of pouchitis (n=60, 65%), CDP (n=32, 34.4%) and cuffitis (n=1, 1%). Effectiveness was evaluated only for thiopurine monotherapy (n=62). After a median follow-up of 23 (1-234) months, clinical remission was achieved in 31%, clinical response in 31% and non-response in 38% (Figure 1). There were no differences in effectiveness between pouchitis and CDP (63.9% vs 57.7%, p= 0.62). Endoscopic response was evaluated in 19 (30.6%) cases. After a median of 9 months of follow-up median PDAI endoscopic subscore dropped from 3 (range 2-4) to 1 (range 0-3), (Figure 2). Adverse events related with treatment appeared in 28 patients (45%). Thiopurines were discontinued in 39 cases (63%) due to failure (17), toxicity (16) and long remission (6 cases). Conclusion: In our cohort, thiopurines were used in 27% of patients with IDP, with long-term benefit (remission or response) in around two-thirds of them. This therapy could be one more option to manage these disorders.